Abdullah Ahmed An-Na’im antara Teologi Islam dan Hak Asasi Manusia (HAM) - arman budiman, Arman (SETYAKI : Jurnal Studi Keagamaan Islam, 2024)
This paper seeks to explore the relationship between Islamic theology and human rights (HAM) in Abdullahi Ahmed An-Na'im's thought and provides an example of human rights violations that occur in modern Muslim societies. Seeing the relationship between Islam and human rights is still a hot topic to be debated and even contested, both from a historical and philosophical-theological point of view. This study examines how Ahmed An-Na'im's Theological Construction and its relevance to the problems of Modern Society. This paper is a library research using historical methods. Meanwhile, in data analysis, the hermeneutic theory was used, while the data sources in this study consisted of primary sources and secondary sources. This study concludes that An-naim made the Universal Declaration of Human Rights a powerful instrument to protect the glory, dignity and worth of every human being on Earth. Indirectly, An-naim seeks to eradicate human rights violations and the examples of human rights violations for modern Muslim societies that we have mentioned in this article clearly violate the right to life and the right to avoid violence. Because in truth humans want to live their lives freely without any acts of violence even to the point of eliminating the lives of citizens. This is very closely related to An-naim's offer to make human values the main element in law and eliminate all acts of violence on earth so that humans can live in peace, peace and comfort.